Feasibility and acceptability of a multi-component mental wellbeing program for young high-performance athletes in Australian Rules Football - Hoare, Erin; Couston, Nicky; Burdon, Lilli; Vella, Claudia; Hall, Kate (Frontiers in Sports and Active Living, 2024)
There is a strong rationale for the promotion of mental wellbeing in elite sport development pathways although evidence-based programs are scant. Scholarly work more broadly indicates the importance of co-design and lived experience in the development of programs targeting mental health and wellbeing for young people. Further, the evidence to date suggests that programs should be multi-component to target the various systems within which young people engage. This study examines the feasibility and acceptability of a multi-component wellbeing program, informed by positive psychology and wellbeing science. The AFL Talent Pathways Wellbeing Program aims to foster positive mental health and wellbeing among young (16–18 year-old) athletes in Australian Rules Football participating in the AFL Talent Pathways. The program was comprised of multiple components including (i) a wellbeing curriculum informed by positive psychology, (ii) strengthened localized dedicated capacities in personnel within football communities, and (iii) an individualized wellbeing development plan. Feasibility and acceptability were assessed through qualitative interviews with young athletes, coaches, and wellbeing coordinators which focused on experiences related to program engagement, satisfaction, participation, and retention. A pre-specified thematic analytical approach was adopted, whereby qualitative interview data were transcribed, and then underwent a six-phase analysis process to assess themes. Results suggested gradual acceptance of the program, with increasing levels of connection and support reported throughout the program delivery. Barriers to engagement included the scheduling of the program content within the context of a comprehensive training schedule and the travel time required to be able to participate in the program particularly for non-metropolitan and regional-based athletes. Strengthening football community capacity for specific wellbeing-related needs was seen as a major facilitator to the acceptability and feasibility of the wellbeing program. These findings, although limited by a small sample size, contribute to the growing evidence body of supporting young athletes transitioning into elite sport and is strengthened through the qualitative insights achieved through the lived experience of program participants.